Technical Report on the New Ultrasound Lateral Mid-Shaft Approach to the Sciatic Nerve: A Never-Ending Story - Giuseppe Sepolvere; Mario Tedesco; Mario Cibelli; Dario Cirillo; Angelo Sparaco; Giuseppe Gagliardi; Giuseppina Costagliola; Loredana Cristiano; Valeria Rita Scialdone; Maria Rosaria Pasquariello; Fabrizio Di Zazzo; Luigi Merola; et al. (Medicina)
The anatomy of the sciatic nerve allows it to be blocked at different levels using various anesthetic approaches. However, for several reasons, performing these approaches may be challenging or disadvantageous in specific categories of patients, particularly in obese patients. The objective of this brief technical report is to describe a new technical approach to sciatic nerve block, designed to simplify the procedure for certain categories of patients and less experienced practitioners. Since 2010, more than 5000 procedures have been performed by both experienced anesthesiologists and novice trainees in several hospitals. The ultrasound lateral mid-shaft technique appears to be a safe and effective method for performing a sciatic nerve block, even in obese patients with significant subcutaneous fat and unclear ultrasound images. This approach is particularly beneficial given the various anatomical variations that can occur. By targeting the mid-thigh area, the ultrasound beam accesses anatomical structures that are more superficial, improving the technique’s efficacy. Various hospital groups have been performing this technique as a routine procedure, achieving a success rate of nearly 100%. This impressive success rate exceeds that of other conventional techniques documented in the literature. Additionally, there have been significant improvements in comfort and ease for anesthetists. This method allows the anesthetic to spread around the paraneural sheath, covering the posterior femoral cutaneous nerve. Finally, it is performed in the supine position without the need to mobilize the lower limbs, ensuring patient comfort, especially in cases of fractures or lower limb injuries. Further studies are needed to confirm these results.